2018
DOI: 10.1007/s10238-018-0522-5
|View full text |Cite
|
Sign up to set email alerts
|

Massive stent thrombosis during active ulcerative colitis: the tricky balance between manifest hemorrhagic and concealed thrombotic risk

Abstract: Inflammatory bowel diseases have been recognized as predisposing factors to atherosclerosis and thrombotic events, involving both the venous and the arterial circulatory systems. We report the case of a 70-year-old man who presented with ST elevation myocardial infarction during the active phase of ulcerative colitis (UC). Because of the ongoing hematochezia, after successful revascularization of the culprit vessel, the patient was medicated with Clopidogrel, in place of one of the more powerful new oral P2Y i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…19 We observe higher rates of BMS use in IBD patients, which could be explained by physicia ns' recognition of the potential higher risk of long-term bleeding in this group and their possibility of early discontinuation of dual antiplatelet therapy. [20][21][22] However, BMS have been shown to be inferior to DES in the long-term with respect to outcomes such as target lesion and vessel revascularization and risk of reinfarction. 23 In the recent years, as an alternative to BMS in high bleeding risk groups, many studies reported favorable outcomes of new stent platforms, as well as new antiplatelet therapy strategies with shorter DAPT duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 We observe higher rates of BMS use in IBD patients, which could be explained by physicia ns' recognition of the potential higher risk of long-term bleeding in this group and their possibility of early discontinuation of dual antiplatelet therapy. [20][21][22] However, BMS have been shown to be inferior to DES in the long-term with respect to outcomes such as target lesion and vessel revascularization and risk of reinfarction. 23 In the recent years, as an alternative to BMS in high bleeding risk groups, many studies reported favorable outcomes of new stent platforms, as well as new antiplatelet therapy strategies with shorter DAPT duration.…”
Section: Discussionmentioning
confidence: 99%
“…As IBD are chronic inflammatory conditions, the full extent of the risk related to it may be underestimated on short-term follow-up 11,12,29 Finally, the NIS database does not include data that may be relevant. It does not include pharmacother ap y; hence we were unable to determine differences in the use of antithrombotic therapy between the study groups or to determine the effect of baseline IBD treatment on clinical outcomes, which may both act as confounders 3,8,20 . The NIS also does not provide certain procedural information such as coronary lesion and procedural complexities, type of DES used (1 st vs 2 nd generation) and extent of revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…При этом риск острых коронарных событий по сравнению с общей популяцией был повышен среди пациентов, как принимаю щих, так и не принимаю щих системные глюкокортикоиды [10]. Риск развития ССО и летальных исходов у пациентов с ВЗК, по данным когортных исследований, значительно увеличивался в период обострений ВЗК [11].…”
Section: Introductionunclassified
“…Thrombosis in IBD is caused by the interaction of many hereditary and acquired risk factors with close link with inflammation. Higher levels of coagulation factors frequently occur in IBD which may predispose to arterial thromboembolic events [ 12 ]. The prevalence of venous thromboembolism (VTE) varies between 1 and 7% among patients with IBD.…”
Section: Introductionmentioning
confidence: 99%